Effect of different drying treatments and different extraction methods on α-glucosidase inhibitory activities of S. zalacca fruit - Siddiqui, Mohammad Jamshed Ahmad; Saleh, Mohammed S M; Mat So'ad, Siti Zaiton (2019)
Introduction: Salacca zalacca (Gaertn Voss), commonly known as snake fruit and belongs to the Arecaceae family and natives of Southeast Asia. This fruit is edible and have certain medicinal values. Objectives: The aim of this study was to compare the α-glucosidase inhibitory activities of different drying and extraction methods. Material and methods: Flesh of this fruit was subjected to two different drying methods namely; oven dried (OD) and freeze dried (FD) and extracts were prepared using soxhlet (SX), sonication (SC) and maceration (MC) techniques. The α-glucosidase inhibitory activity of extracts were evaluated using α-glucosidase enzyme . Results: The S. zalacca fruit extracts obtained through SC and MC demonstrated better α-glucosidase inhibitory activity as compared to SX method, specifically, the FD extracts showed higher activity compared to the OD extracts. Analysis of α-glucosidase inhibitory activity of the OD S. zalacca fruit extract indicates that extract obtained through SC method possesses significantly higher activity (IC50 79.42 µg/mL) than that of SX extracted sample which displayed IC50 at 125.73 µg/mL. Considering the effects of both methods (drying and extraction) on the α-glucosidase inhibitory activity of S. zalacca fruit extracts, extract obtained through SC of the FD fruits demonstrated the highest activity (IC50 19.40 µg/mL) Meanwhile, extracts obtained via OD and different extraction methods such as SX, MC and SC showed the least inhibition with IC50 125.73, 87.23 and 79.42 µg/mL, respectively. Conclusion: This study suggests that S. zalacca fruit has the potential for nutraceutical enhancement and as ingredient in medicinal preparation.